Acceptance and commitment therapy universal prevention program for adolescents: a feasibility study - Rowan Burckhardt; Vijaya Manicavasagar; Philip J. Batterham; Dusan Hadzi-Pavlovic; Fiona Shand (BMC, 2017)
Abstract Background There is a need to prevent anxiety and depression in young people and mindfulness contains important emotion regulation strategies. Acceptance and commitment therapy (ACT), a mindfulness-based therapy, has yet to be evaluated as a prevention program, but has demonstrated an ability to reduce symptoms of anxiety and depression in adult and adolescent populations. This study examines the feasibility of using an ACT-based prevention program in a sample of year 10 (aged 14-16 years) high school students from Sydney, Australia. Methods Participants were allocated to either their usual classes or to the ACT-based intervention. Participants were followed for a period of 5 months post-intervention and completed the Flourishing Scale, Depression Anxiety Stress Scale, and a program evaluation questionnaire. Analyses were completed using intention-to-treat mixed models for repeated measures. Results The results indicated that the intervention was acceptable to students and feasible to administer in a school setting. There were no statistically significant differences between the conditions, likely due to the small sample size (N = 48). However, between-group effect sizes demonstrated small to large differences for baseline to post-intervention mean scores and medium to large differences for baseline to follow-up mean scores, all favouring the ACT-based condition. Conclusion The results suggest that an ACT-based school program has potential as a universal prevention program and merits further investigation in a larger trial. Trial registration Australian New Zealand Clinical Trials Registry. Trial ID: ACTRN12616001383459. Registered 06/10/2016. Retrospectively registered.